Kepemimpinan Wanita Sebagai Kepala Sekolah Studi di SD Negeri Kecamatan Balung Kabupaten Jember - Selasi Priatiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to describe the type of leadership of female principals and teacher perceptions of the leadership style of female principals in State Primary Schools in Balung District. The approach used is a quantitative approach with a survey method to get an overview of the types and styles of leadership of girls' schools. Data collection was carried out using questionnaire techniques and interviews with 54 teachers in 5 public elementary schools headed by female principals. The sampling technique uses saturated sampling using the entire population of 5 schools. The results showed the dominant type of 5 female principals included in the type of personal leadership with a mean of 10,148 (SD 1,393) while the authoritarian type obtained the smallest value to be the minor type chosen by teachers with a mean of 9,056 (1,224). While the teacher's perception shows that the principal's leadership style in SD Negeri Balung District tends to be feminine with a mean of 3.68 and transformational with a mean of 3.11 which is also supported by two indicators of masculine and transactional styles. Conclusions, the dominant type of female headmaster's leadership is 'personal' and 'feminine' and 'transformational' leadership styles. Keywords: Women's Leadership, Women's Principal, Balung Elementary School